Selection of white oat genotypes for contrasting fungicide management conditions - Berlezi, Júlio Daronco; Carvalho, Ivan Ricardo; Silva, José Antonio Gonzalez da; Loro, Murilo Vieira; Sfalcin, Inaê Carolina; Pradebon, Leonardo Cesar; Port, Eduarda Donadel; Ourique, Rafael Soares; Roza, João Pedro Dalla (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to select white oat (Avena sativa) genotypes for environments with and without fungicide application, as well as to identify relationships between meteorological variables and agronomic traits. Two experiments were carried out: one without and the other with the use of the tebuconazole fungicide. In each experiment, 26 genotypes were evaluated, conducted during ten years in the same experimental area; cultivation years were considered as one environment. The methodologies of genotype and of the genotypes x environments interaction were used to define the ideal genotype. 'URS Corona' is considered an ideal genotype due to its excellent responses in the environment with tebuconazole. The 'Brisasul', 'IPR Aphrodite', and 'URS Taura' genotypes respond better in the environment without the fungicide. However, based on multitraits, the 'URS Taura' and 'IPR Afrodite' genotypes can be positioned in environments with or without the use of tebuconazole. Genotypes with a rust incidence lower than 15% and a height higher than 93 cm in an environment with a relative humidity lower than 70.75% have a higher grain yield regardless of fungicide use. Greater magnitudes of air temperature and solar radiation result in a higher grain yield of white oat, regardless of fungicide use.